Frequency of HLA-B27 gene among patients with ankylosing spondylitis and its consequences on clinical manifestation (BIRDEM Medical Journal, 2019)
Background: Ankylosing spondylitis is an inflammatory disease and leading case of back pain worldwide. It is thought that the gene human leukocyte antigen-B27 (HLA-B27) provides a strong tendency in people to develop ankylosing spondylitis. This study was designed to evaluate the frequency of HLA-B27 among patients with ankylosing spondylitis and clinical manifestation among the HLA-B27 positive and negative patients.Methods: A cross-sectional study was done in the Department of Medicine and Department Rheumatology of BSMMU, Shahbag, Dhaka, Bangladesh from 1st January 2016 to 30th June 2016.Results: Total 70 patients were included in this study, among those 54 were male and 16 were female and total 54 patients (77.14%) were HLA-B27 positive and 16 patients (22.86%) were HLA-B27 negative. Most HLAB27 positive patients had extra-articular manifestation, family history of low back pain and high level of BASDAI score, compared to those who were negative. Among the 54 positive patients, 9 (16.67%) had combination of tendinitis, enthesitis and uveitis and 2 (3.70%) had all four of extra-articular manifestation. Among the 16 negative patients, 2 (12.5%) had all four extra-articular manifestation. Among 16 negative patients 9 (56.25%) had raised erythrocyte sedimentation rate (ESR) and 5 (31.25%) had raised C-reactive protein (CRP). On the other hand, among 54 positive patients 48 (88.89%) had raised ESR and 44 (81.48%) had raised CRP.Conclusion: The association of HLA-B27 might be the reason of disease severity among the positive patients.Birdem Med J 2019; 9(3): 188-192